Life History and Exploitation Status of Savalai Hairtail (Lepturacanthus savala) from Lampung Bay Waters - David Julian; Muhammad Reza; Muhamad Gilang Arindra Putra (Jurnal Biologi Tropis, 2026)
The savalai hairtail (Lepturacanthus savala) is a commercially valuable demersal species in the coastal ecosystems of Teluk Lampung, where increasing fishing pressure has raised concerns regarding stock sustainability. This study assessed the life history characteristics and exploitation level of the species to support sustainable fisheries management. An overall number of 347 individuals were obtained from fishing port between May and August 2023. Length-frequency data were analyzed utilizing the TropFishR package with the electronic length frequency analysis (ELEFAN) approach. The results showed that the population exhibits relative growth, consistent with tropical fish characteristics. However, fishing mortality significantly exceeded natural mortality, signifying intense fishing efforts on the stock. The utilization rate has exceeded the optimum level, indicating overexploitation, while biological indicators revealed that many individuals were captured prior to attaining adequate reproductive size, posing a threat of recruitment overfishing. These findings demonstrate that the savalai hairtail stock in Teluk Lampung is not sustainable under current exploitation levels. Immediate management actions, including controlling fishing effort, improving gear selectivity, and protecting immature fish, are urgently required to guarantee the long-term viability and stop additional stock depletion of fisheries resources in Teluk Lampung.